Emotional Experience and Type of Communication in Oncological Children and Their Mothers: Hearing Their Testimonies Through Interviews - Barrios, Paula; Enesco, Ileana; Varea, Elena (Frontiers in Psychology, 2022)
The emotional experience and the level of communication about cancer within the family are important factors for successful coping with pediatric oncology. The main purpose is to study mother’s and children’s emotional experiences concerning cancer, whether they communicate openly about the disease, and relationships between the degree of communication and the different emotions expressed by the children. Fifty-two cancer-patients aged 6 to 14 years and their mothers were interviewed in separate sessions about the two central themes of the study: emotional experiences and degree of communication. Analyses of response categories were performed to subsequently compare the age groups and the mother-child responses. According to the results, mothers expressed emotions such as fear, sadness, or anxiety, while children report sadness, pain, but also happiness. Significant positive correlations were observed between mothers' sadness and older children's sadness, mothers' anxiety and children's fear, and mothers’ anxiety and children’s happiness. Regarding communication style, mothers tend to hide information about the disease from younger children and to provide direct information to the older children. Children usually prefer to communicate their concerns to parents; however, children whose mothers convey anxiety are more likely to prefer to communicate with others. These results support the idea that parents should talk honestly with their children, explaining their illness in an age-appropriate way, and encouraging them to share their emotional experiences. Further studies are needed from a developmental perspective to understand the disease management of children and families.